2020
DOI: 10.1177/0021998319899153
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cure parameters in polymer matrix composites using embedded optical fibers

Abstract: The influence of cure processing parameters was investigated using strain distributions from embedded optical fibers. The determination of optimized cure parameters is often needed to achieve material properties which meet aerospace industry design requirements. Optical fibers were embedded near the midplane of thin (5 mm; [0/90/90/0]3s) composite laminates to monitor the internal strain during cure for two different cure cycles (manufacturer-recommended and an alternative two-step cure). Each laminate was fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Drake et al studied the influence of a longer two-step cure cycle on an amine-based aromatic resin and concluded that altering the cure cycle from one step to two steps changed the formation of the polymer networks during cure with reduced thermal residual strains in the laminates. 89 Similar behaviors were concluded by Timmerman et al in a study that investigated the effects of cure temperature on cryogenic microcracking of PMCs. 90 Higher cure temperatures resulted in higher stress-free temperatures, residual strains, and glass transition temperatures in the composites.…”
Section: Permeability and Transverse Microcrackingsupporting
confidence: 76%
“…Drake et al studied the influence of a longer two-step cure cycle on an amine-based aromatic resin and concluded that altering the cure cycle from one step to two steps changed the formation of the polymer networks during cure with reduced thermal residual strains in the laminates. 89 Similar behaviors were concluded by Timmerman et al in a study that investigated the effects of cure temperature on cryogenic microcracking of PMCs. 90 Higher cure temperatures resulted in higher stress-free temperatures, residual strains, and glass transition temperatures in the composites.…”
Section: Permeability and Transverse Microcrackingsupporting
confidence: 76%
“…The improvement of the component quality has been pursued introducing new materials in the product design. 1,2 In this perspective, the prominence of composite materials was widely explained. 3 Fiber reinforced polymers (FRPs) are the most investigated and employed reinforced materials.…”
Section: Introductionmentioning
confidence: 99%